Nadir ka ghar - Maryam, Shera; Shireen, Syed (book group Karachi, 1998)
Nadir Ka Ghar (Nadir's House) is likely a children's book in Urdu that introduces young readers to the concept of home and family. The story might revolve around Nadir's daily life at home, his family members, and the activities they do together. It could also explore the different rooms in a house, their functions, and the importance of keeping the house clean and tidy.